Patterns of liver injury in HIV-positive patients in the medical admissions ward at Chris Hani Baragwanath Academic Hospital (CHBAH) - Ndwambi, Rudzani Wendy (University of the Witwatersrand, Johannesburg, 2024)
Background Human immunodeficiency virus (HIV) infection is a major global public health concern, with approximately 37.9 million people living with HIV and acquired immunodeficiency syn- drome (AIDS) as of 2018. There has been an increase in HIV prevalence globally, with the African sub-Saharan region carrying a disproportionate burden, accounting for more than 70% of this burden. In 2018 South Africa had 7.52 million people living with HIV/AIDS (PLWHA), with approximately 115167 AIDS-related illnesses. In PLWHA, liver disease and failure contribute to more significant morbidity, mortality and higher cost of care. Aim And objectives To recognise and categorise the patterns of liver injury in people living with HIV and AIDS (PLWHA). To ascribe an etiology to the pattern of liver injury in PLWHA. Method This was a retrospective cohort, conducted at CHBAH medical admissions ward in Soweto Gauteng province, of patients living with HIV and AIDS with liver injury. All patients admitted to the medical admissions ward were selected and their hospital numbers retrieved from the admission register. Each hospital number was entered into the NHLS labtrack system to retrieve the LFT results. Any patient with abnormal LFT was checked for their HIV status. The two variables (abnormal LFT and HIV test) were matched and confirmed. After ethics approval was obtained, files were recorded and analysed. A data collection sheet was populated with all serological, histological and radio logical investigations documented. Results This study included 208 patients (PLWHA) admitted to the medical admissions ward at CHBAH, with abnormal liver enzymes between January 2019 and March 2020, aged above 18 years. One hundred and five, 50.5% were males with a mean of 43.7 years, and 49.5% (n=103) were females with a mean of 39.9 years. One hundred and forty-three, 81.3% were taking antiretroviral therapy (ART), with the majority, 88.4% (n=107), on the first-line regimen. The most common pattern of liver injury was infiltrative, accounting for 67.8% (n=141), followed by mixed at 22.1% (n=46), hepatocellular at 7.7% (n=16), and lastly was cholestatic with 2.4% (n=5). Irrespective of the pattern of the liver injury, 36.1% (n=75) of the patients had Mycobacterium tuberculosis (MTB) infection, and 22.5% (n=40) of them were on antituberculosis treatment (ATT), 6.3% (n=13) had hepatitis B viral (HBV) infection, 0.5% (n=1 ) had hepatitis C ( HCV) infection, while lymphomas (Hodgkin and non-Hodgkin lymphomas) contributed 1,9%(n=4) and 6,3% (n=13) respectively. Twelve, 5.7% (n=12) had drug induced liver Injury (DILI), and retroviral disease (RVD) cholan giopathy contributed 1.4% (n=3). A significant number of patients, 34.1% (n=71), contributed to at least one-third of patients in the study, wherein the diagnosis was either unknown or not directly related to the liver injury. Those were, Other opportunistic infections accounting for 7.7% (n=16), other diagnoses made up 13% (n=27), and no diagnosis at 13.4% (n=28). Of the infiltrative pattern, 33.13% (n=47) had MTB infection, 5.6% (n=8) had HBV, 0.3% (n=1) had HCV infection, 7.8% (n=11) had non-Hodgkin lymphoma, with Hodgkin lym- phoma, and DILI both accounting for 1,4%(n=2). Only 5.7% (n=12) of PLWHA had liver biopsies done. Conclusion Liver injury is common in PLWHA. The most common pattern of liver injury is an infiltrative pattern, and the most common etiology was MTB infection in this study.
A research report submitted in partial fulfillment of the requirements for the Degree of Masters of Medicine in Internal Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: Human immunodeficiency virus (HIV); HIV; UCTD; SDG-3: Good health and well-being